Peatlands in Chilean Patagonia: Distribution, Biodiversity, Ecosystem Services, and Conservation - Mansilla Andrade, Claudia Andrea; Domínguez, Erwin; Mackenzie Calderon, Roy; Hoyos, Jorge; Henriquez Troncoso, Juan Marcos; Aravena Donaire, Juan Carlos; Villa Martinez, Rodrigo Patricio (My University, 2021)
Peatlands are wetland ecosystems characterized by the accumulation of large amounts of organic matter over centuries and millennia; they are the most important long-term carbon sink in terrestrial ecosystems. Peatlands are also valuable ecosystems for biocultural and biodiversity conservation, as paleo-climatic archives, and as providers of ecosystem services to human society.
Keywords: Patagonia; Chile; Turberas; Biodiversidad; Servicios Ecosistémicos; Reservorio De Carbono; Sphagnum; Extracción De Turba